The Influence Of Social Media Marketing On Purchase Intention With E-Wom And Brand Awareness As Intervening Variables On Indibiz Services (Instagram @Indibiz.Id) - Rifki Hariadi, Maghfira; Ariyanti, Maya (International Journal of Science, Technology & Management, 2025)
The development of digital technology and social media has changed consumer behavior in making purchases, including business to business marketplaces that can help the business world in Indonesia, especially small and medium enterprises (SMEs) go digital and move up a class, one of which is Indibiz. The presence of Indibiz has not been fully socialized in the MSME community, resulting in a lack of understanding of the added value offered by the product. This study aims to analyze the influence of social media marketing on purchase intention with brand awareness and e-WOM as intervening variables in Indibiz services. This study uses a quantitative approach with data collection techniques through questionnaires. The research sample was active followers of Instagram @indibiz.id totaling 400. Data were analyzed using Structural Equation Modeling PLS. The results of the study showed there is a positive and significant influence between Social Media Marketing on e-WOM, Brand Awareness, and Purchase Intention. There is also a positive and significant influence of e-WOM on Brand Awareness. In addition, e-WOM and Brand Awareness contribute significantly to purchase intention. e-WOM and Brand Awareness also play a role in mediating the relationship. These results emphasize the importance of managing marketing on social media to strengthen relationships with MSMEs and increase purchase intention.